Step-by-step explanation:
4x2=−9x−4
Step 1: Subtract -9x-4 from both sides.
4x2−(−9x−4)=−9x−4−(−9x−4)
4x2+9x+4=0
For this equation: a=4, b=9, c=4
4x2+9x+4=0
Step 2: Use quadratic formula with a=4, b=9, c=4.
x=
−b±√b2−4ac
2a
x=
−(9)±√(9)2−4(4)(4)
2(4)
x=
−9±√17
8
x=
−9
8
+
1
8
√17 or x=
−9
8
+
−1
8
√17
Answer: ill try looking this one up to help u just add me on snap its johni_spurgeon
Step-by-step explanation:
Answer:
16 + 3n
Step-by-step explanation:
a = 19 ; common difference = 22 - 19 = 3
a(n) = a + (n -1 ) *d
= 19 + (n-1)*3
= 19 + 3n - 3
= 16 + 3n